Ralph Vaughan Williams and Adrian Boult - Simeone, Nigel 1956- (The Boydell Press, 2022)
The first detailed study of the working relationship and productive friendship between Ralph Vaughan Williams (1872-1958) and Adrian Boult (1889-1983)